Elevated tricuspid regurgitation velocity in congenital hemolytic anemias: Prevalence and laboratory correlates. Issue 7 (25th March 2019) - Yates, Amber M.; Joshi, Vijaya M.; Aygun, Banu; Moen, Joseph; Smeltzer, Matthew P.; Govindaswamy, Devi; Dowdy, Jola; Cotton, Alyssa; Kang, Guolian; Ware, Russell E.; Hankins, Jane S.
Abstract: Elevated tricuspid valve regurgitation jet velocity (TRV ≥ 2.5 m/s) is associated with mortality among adults with sickle cell disease (SCD), but correlative biomarkers are not studied according to treatment exposure or genotypes. To investigate the associations between biomarkers and TRV elevation, we examined the relationship between TRV and hemolytic, inflammatory, and cardiac biomarkers, stratified by disease‐modifying treatments and SCD genotype. In total, 294 participants with SCD (mean age, 11.0 ± 3.7 years) and 49 hereditary spherocytosis (HS; mean age, 22.9 ± 19.75 years) were included for comparison and enrolled. TRV was elevated in 30.7% of children with SCD overall: 18.8% in HbSC/HbSβ + ‐thalassemia, 28.9% in untreated HbSS/HbSβ 0 ‐thalassemia, 34.2% in HbSS/HbSβ 0 ‐thalassemia hydroxyurea‐treated, and 57% in HbSS/HbSβ 0 ‐thalassemia chronic transfusion treated. TRV was elevated in 10.7% and 27.8% in HS children and adults, respectively. In children with SCD, elevated TRV was correlated with hemoglobin (odds ratio [OR] = 0.78, P = 0.004), lactate dehydrogenase (LDH; OR = 2.52, P = 0.005), and N‐terminal pro‐brain natriuretic peptide (NT‐pro BNP; OR = 1.003, P = 0.004). In multivariable logistic regression, adjusting for genotype, sex, hemolytic index, and treatment, hemoglobin concentration remained the only significant variable associated with elevated TRV in untreated HbSS/HbSβ 0 ‐thalassemia participants. TRV was not associated with inflammatory markers, other markers of hemolysis, or NT‐pro BNP in untreated HbSS/HbSβ 0 ‐thalassemia. Neither hemoglobin nor LDH was associated with TRV in HbSC/HbSβ + ‐thalassemia. These results suggest that elevated TRV is influenced by the degree of anemia, possibly reflecting sickling as part of the disease pathophysiology. Prospective studies should monitor hemoglobin concentration as children with SCD age into adulthood, prompting initiation of TRV screening and monitoring.